MECHANISMS OF LYSOSOMAL ENZYME RELEASE FROM HUMAN LEUKOCYTES : I. Effect of Cyclic Nucleotides and Colchicine - Zurier, Robert B. (The Rockefeller University Press, 1973)
In order to study mechanisms underlying selective enzyme release from human leukocytes during phagocytosis, the effects were studied of compounds which affect microtubule integrity or the accumulation of cyclic nucleotides. Human leukocytes selectively extrude lysosomal enzymes (β-glucuronidase) from viable cells during phagocytosis of zymosan or immune complexes, or upon encounter with immune complexes dispersed along a non-phagocytosable surface such as a millipore filter. In each circumstance, lysosomal enzyme release was reduced by previous treatment of cells with pharmacological doses of drugs which disrupt microtubules (e.g. 10(-3)–10(-5) M colchicine) or with agents which affect accumulation of adenosine 3'5'-monophosphate (cAMP) (e.g. 10(-3) M cyclic nucleotides and 2.8 x 10(-4)–2.8 x 10(-6) M prostaglandin E (PGE) and A (PGA) compounds). Preincubation of cells with 5 µg/ml cytochalasin B resulted in complete inhibition of zymosan ingestion, but not of adherence of zymosan particles to plasma membranes or selective enzyme release. In this system, in which enzyme release was independent of particle uptake, preincubation of cells with colchicine, vinblastine, dibutyryl cAMP, or PGE(1) also reduced extrusion of lysosomal enzymes. When cell suspensions were incubated with membrane-lytic crystals of monosodium urate (MSU), cytoplasmic as well as lysosomal enzymes were released with subsequent death of the cells. However, enzyme release followed phagocytosis of crystals (as measured by enhanced C-1 oxidation of glucose) and was due to "perforation from within" of the lysosomal membrane, rather than lysis by crystals of the plasma membrane. Enzyme release after MSU ingestion was also reduced when cells were treated with pharmacological doses of the test agents. When cells were killed by Triton X-100, acting on the plasma membrane, C-1 oxidation of glucose was abolished and enzyme release could not be inhibited pharmacologically. These observations suggest that lysosomal enzyme release from human phagocytes can be an active process which accompanies plasma membrane stimulation, is independent of cell death, and may be controlled by cyclic nucleotides and agents which affect microtubules.